Strategising stakeholder empowerment for effective co-management within fishery-based commons. Issue 11 (31st July 2018) - Freeman, Edward Robert; Civera, Chiara; Cortese, Damiano; Fiandrino, Simona
Abstract : Purpose: The purpose of this paper is to link empowerment to the engagement of low-power stakeholders in the context of marine protected areas (MPAs) to suggest how empowerment-based engagement can be strategised to prevent and overcome management crises within a natural common good and ultimately achieve effective co-management. Design/methodology/approach: This research employs a longitudinal case study methodology. The subject of the study is Torre Guaceto MPA, a natural common good, internationally recognised as a best practice of co-management. Findings: The case study illustrates specific empowerment areas and actions that help move low-power stakeholders to higher levels of engagement to achieve effective co-management. It also suggests that the main strategic implication of empowerment-based engagement is the creation of empowered stakeholders who can serve as catalysts for sustaining the common through the development of entrepreneurial skills that satisfy joint interests. Research limitations/implications: The applied methodology of a single case and the peculiar conditions intrinsic to this case can be overcome via the inclusion and comparison of other similar commons. Practical implications: The study provides a stakeholder management model of empowerment-based engagement that offers concrete evidence of empowerment strategies that can be adopted and adapted by the management of similar natural common goods. Originality/value: The research fills the literature gaps related to understanding the antecedents of engagement and its strategic implications within natural common pool resources.